2022
DOI: 10.3389/fpubh.2021.757089
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Revamping of Chronic Respiratory Diseases in Low- and Middle-Income Countries

Abstract: Low- and middle-income countries (LMICs) endure an asymmetrically high burden of worldwide disease and death caused by chronic respiratory diseases (CRDs), i.e., asthma, emphysema, bronchiectasis, and post-tuberculosis lung disease (PTLD). CRDs are firmly related with indigence, infectious diseases, and other non-communicable diseases (NCDs) and add to complex multi-disease with great impact on the lives and livelihood of those affected. The pertinence of CRDs to health and demographic wellbeing is relied upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 139 publications
(150 reference statements)
0
7
0
Order By: Relevance
“…The situation is even more dramatic in low and middle-income countries, where 80% of COPD cases get undiagnosed in clinical care. 50 WHO Noncommunicable Disease Global Action Plan addressed the necessity for diagnostic tools for noncommunicable diseases that were affordable, reliable, and safe and showed improved disease diagnostic capacity and human resources. 51 In 2003, WHO coined the well-known ASSURED criteria (affordable, sensitive, specific, user-friendly, rapid and robust, equipment-free, and ready to be delivered) that a diagnostic tool in the developing world should fulfill to guide disease management effectively.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is even more dramatic in low and middle-income countries, where 80% of COPD cases get undiagnosed in clinical care. 50 WHO Noncommunicable Disease Global Action Plan addressed the necessity for diagnostic tools for noncommunicable diseases that were affordable, reliable, and safe and showed improved disease diagnostic capacity and human resources. 51 In 2003, WHO coined the well-known ASSURED criteria (affordable, sensitive, specific, user-friendly, rapid and robust, equipment-free, and ready to be delivered) that a diagnostic tool in the developing world should fulfill to guide disease management effectively.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The deployed implementation of compact analytical platforms that enabled the quantitative simultaneous detection of several biomarkers could have a huge impact on effective disease management by improving the underdiagnosis and misdiagnosis rates and in turn alleviating the economic burden on the healthcare systems. The situation is even more dramatic in low and middle-income countries, where 80% of COPD cases get undiagnosed in clinical care …”
Section: Discussionmentioning
confidence: 99%
“…Mortality distribution was highest for LMIC in the African continent, while Philippines, Maldives and Thailand were among the leading in APR. A recent review on chronic respiratory diseases found a staggering 96% of asthma‐related deaths and 84% of disability‐adjusted life years (DALY) worldwide in LMICs 17 …”
Section: Asthma Prevalence and Disease Burdenmentioning
confidence: 99%
“…A recent review on chronic respiratory diseases found a staggering 96% of asthmarelated deaths and 84% of disability-adjusted life years (DALY) worldwide in LMICs. 17 A Lancet review on asthma in LMICs has shown that although asthma ranked as the 28th most common cause of disability-adjusted years of life lost (YLL) worldwide in 2015, it was the 8th highest cause of YLL in Oceania (Fiji, Kiribati, Marshall Islands, Micronesia, Papua New Guinea, Samoa, Solomon Islands, Tonga, Vanuatu). 8 The review also found that many adult asthmatics are only identified in emergency rooms and there is lack of proper follow-up and treatment.…”
Section: Burdenmentioning
confidence: 99%
“…Exposure to biomass fuel smoke, ambient air pollution, and smoking are the key risk factors of CRDs 3 . The burden of CRDs is disproportionately high in low‐ and middle‐income countries (LMICs), considering the ampler presence of risk factors, lack of knowledge and awareness of the disease, and its risk factors at the population level, which is further challenged by the lack of health system capacity to prevent and manage the rising burden of CRDs 4 . Most CRD‐related deaths occur in Asian countries, with approximately 75% of all cases 2 .…”
Section: Introductionmentioning
confidence: 99%